Sustainable Energy Cyclic System: Massive Operation and Integrated System for Optimizing Renewable Energy Sources - Ratri Rahmawati; Muhammad Faris; Muhammad Ibrahim; Nita Andriyani Budiman; Rianto Wibowo; Rochmad Winarso (Universitas Pendidikan Mandalika, 2023)
Energy as basic need for life indeed face crisis of scarcity. Yet, the idea of using renewable energy becomes popular for example hydropower, solar energy, side product (i.,g biomass and domestic waste) that have been introduced. Each of them have advantages and found reliable to be implemented. Ascribe to the concept of law conservation of energy, these potentials can be integrated and be optimized to create energy cyclic system. Hence, this study introduces the concept of sustainable energy cyclic system by accommodating several resources namely hydropower, human side products, biomass and solar energy. This study used comprehend data which then analysed to purpose the idea. Data were collected and were projected to the focus of study. It is addressed to create systematic system of energy yet hampering energy crisis. This study shows that the idea to generate sustainable energy cyclic is reliable in which it compiles each of potential and integrates into systematic system. Moreover, the energy cyclic provides the sustainable solution facilitated by abundant resources such as human side product, biomass, hydropower, solar power, and salinity gradient energy.